الحماية القانونية للوظيفة العامة من الفساد الإداري في ظل الشريعة الإسلامية وقانون دولة الإمارات العربية المتحدة - (دراسة مقارنة) . - علي سيف علي بن غافان آل علي
Due to the growing corruption behaviors that destroy the nerve of the administration and the state, hinder its growth and development, threaten its security, and the disintegration of its societies, there is an urgent need to protect the public function and public money from these risks that threaten them as one of the main pillars in building states. The problem of the research lies in the fact that the United Arab Emirates, just like the rest of the world and the United Nations, has moved at the local, Gulf, regional, and international levels, to combat corruption by merely enacting legislation and local laws that criminalize administrative corruption behaviors and prosecute the perpetrators and apply penalties to them. This move, however, does not work due to the continuous development of administrative corruption. Through his thesis, the researcher hopes that the UAE will adopt the thesis proposal by establishing a ministry or a public body specialized in combating corruption in general and administrative corruption in particular. To ensure that this research can achieve the research objectives and further uncover the research problem, the researcher used several approaches namely the inductive, comparative, and analytical approaches. For the researcher, the importance of the study for the authorities and individuals in the UAE society and in the world, in general, highlights the importance of the existence of competent bodies or organs to combat administrative corruption and its impact on these crimes. The researcher concluded that the countries that have anti-corruption administrative agencies have made significant progress in the fight against administrative corruption, and these countries also present a better position in the corruption perception index. The researcher recommends all countries establish anti-corruption administrative bodies, and Islamic countries should develop a working basis for anti-corruption administrative bodies derived from Islamic law.